Nizza 1985 - Girosi, Elena; Fagioli, Massimo (Il sogno della farfalla, 2016)
Carrying on the publication of texts by Massimo Fagioli, which have still not been made available in print, here we propose the transcription of Massimo Fagioli’s intervention at the opening of the exhibition called “L’Italie aujourd’hui/Italia oggi” (Italy nowadays), which took place in Nice on June 14th, 1985. As Elena Girosi recalls in the introduction, a large number of people from Analisi Collettiva attended the meeting. In his intervention, Fagioli highlighted the reactions the event caused in itself and dwelt on the theme of the artist’s identity and on the unconscious dynamics his or her presence would arise in society.